Dinamika agama lokal di Indonesia - INDONESIA_Kementerian_Agama_RI_Badan_Litbang_dan_Diklat_Puslitbang_Kehidupan_Keagamaan (Puslitbang Kehidupan Keagamaan Badan Litbang dan Diklat Kementerian Agama RI, 2014)
st,2/ws.c.1-2